New constitutionalism in Latin America promises and practices - Nolte, Detlef; Schilling-Vacaflor, Almut (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2012)
The book also covers sociopolitical settings, which factors and actors are relevant for the reform process, and analyzes the constitutional practices after reform, including the question of whether the recent constitutional reforms created new post-liberal democracies with an enhanced human and social rights record, or whether they primarily serve the ambitions of new political leaders